ANALISIS PENGARUH INTERNAL CASH FLOW, INTENSITAS MODAL, INSIDER OWNERSHIP, UKURAN PERUSAHAAN, RISIKO BISNIS, DAN PERTUMBUHAN PENJUALAN TERHADAP CAPITAL EXPENDITURE (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Yuanita Ayu, 12.05.52.0061; Nuswandari, Cahyani (Students Journal of Accounting and Banking, 2016)
The study examines the effect of internal cash flow, capital intensity, insider ownership, company size, bussines risk, sales growth on capital expenditure. This research was conducted at the Indonesian Stock Exchange by using a go public manufacturing company as the unit of analysis. The population are go public manufacturing company listed in Indonesian Stock Excahnge with observation period from 2012 until 2014. The sampling method used purposive sampling with the observation period from 2012 to2014. Relationship and (or) influence between variables is describe by using multiple regression analysis.Â The result showed that capital intensity, company size and sales growth are positive significant to capital expenditure. In different way internal cash flow, insider ownership, and bussines risk are not significant to capital expenditure.Keywords: Internal Cash Flow, Capital intensity, Insider Ownership, Company Size, Bussines Risk, Sales Growth, Capital Expenditure